2018
DOI: 10.1029/2018ja025262
|View full text |Cite
|
Sign up to set email alerts
|

Internal Versus External Sources of Plasma at Saturn: Overview From Magnetospheric Imaging Investigation/Charge‐Energy‐Mass Spectrometer Data

Abstract: Plasma composition observations provide a useful mechanism for investigating plasma sources and subsequent evolution within planetary magnetospheres. While He ++ is the second most abundant ion species in the solar wind, there are no known sources of He ++ ions within the magnetosphere of Saturn, allowing He ++ to serve as a tracer of solar wind ions within the Kronian magnetosphere. Meanwhile, water group ions (W + , consisting of O + , OH + , H 2 O + , and H 3 O + ) and H 2 + , known to originate within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 84 publications
(152 reference statements)
4
27
1
Order By: Relevance
“…The heavier ions will be more affected, since they are more confined to the current sheet than other lighter ions and thus subject to reconnection. The average hot ion O + pressure calculated in this study is lower in the dawnside region, where Allen et al () found a depletion of water group hot ions.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…The heavier ions will be more affected, since they are more confined to the current sheet than other lighter ions and thus subject to reconnection. The average hot ion O + pressure calculated in this study is lower in the dawnside region, where Allen et al () found a depletion of water group hot ions.…”
Section: Discussioncontrasting
confidence: 39%
“…This plasma could also reconnect to the external solar wind stream (Dungey, ) that would accelerate the plasma antisunward and down the magnetotail. Ion densities in the magnetotail measured by the CHEMS instrument indicate lower water group ion density in the dawn sector relative to dusk, which could imply reconnective mass loss during the transit of water group plasma across the magnetotail (Allen et al, ) but not necessarily antisunward plasma release.…”
Section: Introductionmentioning
confidence: 99%
“…Mass loss has been shown to occur through periodic reconnection events (Cowley et al, ), in the form of plasmoids (Jackman et al, ) or constantly from the postmidnight sector that is not necessarily related to reconnection (A. W. Smith et al, ). The lower W + density toward the dawn (compared to dusk) in the Allen et al () study is indicative of a magnetotail reconnection that favors mass loss through tailward plasmoids (Mitchell et al, ). Compared to W + , the H + , He + , and He ++ particles exhibit different behavior in the Allen et al () data set: the densities are increased toward the dawn sector, indicating that their sources outweigh the losses, that is, either due to additional energization of thermal plasma up to 32 keV or solar wind plasma entering the magnetosphere.…”
Section: Solar Wind Tracers and Their Implicationsmentioning
confidence: 95%
“…The focus of the Allen et al () study is on the interplay between external and internal charged particle sources in Saturn's magnetosphere from the perspective of suprathermal ions, that is, integrated fluxes and densities of 32 to 220 keV energetic ion populations measured by the Charge Energy Mass Spectrometer, a unique detector that measures ion masses and their charged states at such high energies (Krimigis et al, ), over an extended time period of ∼13 years (2004–2017). The authors exploit a robust method toward determining the relative abundances and group abundance ratios of protons ( H + ), water group ions (W + ), and H 2+, He + , and He ++ near the equatorial plane (±15° in Latitude) for various local times and radial distances covered by the Cassini orbits, <70 Rs toward the magnetotail, adopting a conservative magnetopause boundary by the use of the Kanani et al () model: out to ∼20 Rs in the noon sector and ∼30–45 Rs in the postdusk and predawn sectors (see black line in Figure b).…”
Section: Internally Sourced Ion Distributionsmentioning
confidence: 99%
See 1 more Smart Citation